Is Restless Legs Syndrome Associated with an Increased Risk of Mortality? A Meta-Analysis of Cohort Studies. (19th July 2019) - Cubo, Esther; Gallego-Nieto, Cesar; Elizari-Roncal, Miren; Barroso-Pérez, Teresa; Collazo, Carla; Calvo, Sara; Delgado-López, Pedro David
Background: Restless legs syndrome (RLS) is a common sleep disorder, . although controversial, growing evidence relates the presence of RLS to an increased risk of mortality, mainly due to cardiovascular events. The aim of this article was to review the role of RLS as a risk factor of mortality according to independent cohort studies. Methods: We performed a literature review via PubMed database for articles relating RLS and mortality. We used the random-effects model to calculate the pooled effect estimates on mortality. Heterogeneity between studies was assessed using quantitative and qualitative analysis. Results: Out of 100 articles identified, 13 were finally included. Although studies were heterogeneous ( p = 0.001), no significant publication bias was found. When all cohort studies were considered, the random-effects model yielded a significantly increased risk of mortality in RLS versus non-RLS patients (13 studies, hazard ratio [HR] = 1.52, 95% confidence interval [CI] 1.28–1.80). However, this association was not statistically significant when only cohort studies using the international RLS diagnostic criteria were considered (5 studies, HR = 1.63, 95% CI 0.94–2.81). Discussion: The results of this meta-analysis suggest that RLS seems to be a risk factor of mortality, although this association is conditioned by the diagnostic criteria used in the studies. Future long-term follow-up standardized mortality studies are needed to address this important question that carries potential impact on population global health.